Maternal Satisfaction and Associated Factors with Postcesarean Section Pain Management: A Cross-Sectional Study - Biruk Adie Admass; Fikadu Tadesse Diress; Demeke Yilkal Fentie; Nigussie Simeneh Endalew (Anesthesiology Research and Practice)
Background. Maternal satisfaction with pain management after cesarean delivery serves as an indicator of the quality of care. Assessing the level of satisfaction with postcesarean delivery pain management is paramount for both the mother and the healthcare institution. This study aimed to assess maternal satisfaction with postcesarean section pain management and associated factors at the Comprehensive Specialized Hospital in Northwest, Ethiopia, in 2023. Methods. An institution-based cross-sectional study was conducted from April to June 2023, involving 424 study participants. A consecutive sampling method was utilized for participant selection. Data were entered into Epidata and then exported to SPSS version 25 for analysis. Descriptive and analytic statistics were employed. Both bivariable and multivariable logistic regression analyses were conducted to identify factors associated with maternal satisfaction regarding postcesarean section pain management. Variables with a p value of <0.2 in the bivariable analysis were included in the multivariable analysis. In the multivariable analysis, variables with a p value of <0.05 were considered statistically significant. Crude odds ratio and adjusted odds ratio with 95% confidence intervals were calculated to demonstrate the strength of the association. Results. A total of 424 participants were included in the study with a response rate of 97.8%. The overall maternal satisfaction with postcesarean section pain management was 80.2% (95% CI: 76.1%–83.8%). Urban residence, elective cesarean section, mild pain, two and above previous history of cesarean section, and waiting less than 30 minutes to get analgesia were associated with maternal satisfaction with postcesarean section pain management. Conclusion. The overall maternal satisfaction with postcesarean section pain management was promising. Urban residence, elective cesarean section, previous history of cesarean section, mild pain, and waiting less than 30 minutes to get analgesia were predictor factors for maternal satisfaction with postcaesarian section pain management. We recommend that the stakeholders should give attention to enhancing maternal satisfaction.